Dysregulated monocyte compartment in PACS patients - Kronstein-Wiedemann, Romy; Teichert, Madeleine; Michel, Elisa; Berg, Janina; Robinson, George; Tausche, Kristin; Kolditz, Martin; Bergleiter, Johannes; Thiel, Jessica; Koschel, Dirk; Künzel, Stephan R.; Hölig, Kristina; et al. (Frontiers in Immunology, 2025)
Introduction1-5% of all patients with COVID-19, a disease caused by infection with Severe Acute Respiratory Syndrome Virus 2 (SARS-Cov-2), even those with mild COVID-19 symptoms, continue to have symptoms after initial recovery. Symptoms associated with the post-acute sequelae of COVID-19 (PACS) include, among others, fatigue, shortness of breath, cough, and cognitive dysfunction. Since the dysregulated immune response appears to be caused by the sustained activation of certain immune cells, including monocytes, and the release of specific cytokines, the aim of our study was to investigate the effect of PACS disease on monocyte subpopulations.MethodsTwenty-two healthy and thirty-two patients with PACS were included into this study. We performed blood gas analysis and measured hematological parameters from peripheral blood of PACS patients and compared them with healthy donors. Surface markers to identify monocyte subpopulations were analyzed by flow cytometry.ResultsPACS patients had higher numbers of intermediate and CD56+ monocytes, whereas the numbers of total monocytes, classical and non-classical monocytes were normal compared to healthy donors. Comparison of patients with and without fatigue, cough, and dyspnea showed no difference in monocyte subset frequencies. However, patients with cognitive dysfunction had increased numbers of non-classical monocytes compared to patients without this symptom.DiscussionThis suggests a disturbed homeostasis of the monocyte subsets in the peripheral blood of patients with PACS.